2014
DOI: 10.1002/per.1951
|View full text |Cite
|
Sign up to set email alerts
|

Studying Changes in Life Circumstances and Personality: It's about Time

Abstract: Most theories of personality development posit that changes in life circumstances (e.g. due to major life events) can lead to changes in personality, but few studies have examined the exact time course of these changes. In this article, we argue that time needs to be considered explicitly in theories and empirical studies on personality development. We discuss six notions on the role of time in personality development. First, people can differ before the event. Second, change can be non‐linear and discontinuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
290
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 244 publications
(300 citation statements)
references
References 105 publications
(144 reference statements)
7
290
1
2
Order By: Relevance
“…Indeed, research has shown that traits can predict the occurrence of life experiences (Luhmann, Orth, Specht, Kandler, & Lucas, 2014;Specht et al, 2011). For example, being very sociable in young adulthood increases the probability of starting the first romantic relationship (Neyer & Lehnart, 2007).…”
Section: Life Experiences and Personality Trait Change In "Natural" Smentioning
confidence: 99%
“…Indeed, research has shown that traits can predict the occurrence of life experiences (Luhmann, Orth, Specht, Kandler, & Lucas, 2014;Specht et al, 2011). For example, being very sociable in young adulthood increases the probability of starting the first romantic relationship (Neyer & Lehnart, 2007).…”
Section: Life Experiences and Personality Trait Change In "Natural" Smentioning
confidence: 99%
“…Moreover, although the sample sizes of the present research were not small, in future research larger samples would be desirable because this also would facilitate the sampling of rare events. In addition, larger samples would allow the use of propensity score matching (Rosenbaum & Rubin, 1983;Thoemmes & Kim, 2011), a method that can strengthen the validity of causal conclusions about the effects of life events in observational studies (see also Luhmann, Orth, Specht, Kandler, & Lucas, 2014).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In the analyses, we operationalized selection effects as the predictive effect of self-esteem and narcissism measured at one of the assessments (e.g., Wave 1) on the occurrence of stressful life events in a subsequent period (e.g., the interval between Wave 1 and Wave 2). Socialization effects have been defined as the prospective effect of life events on change in a personality construct Specht et al, 2014), consistent with how socialization effects have been tested in previous research (e.g., Headey & Wearing, 1989;Lüdtke et al, 2011;Magnus et al, 1993;Specht et al, 2011). In the analyses, we operationalized socialization effects as the predictive effect of the occurrence of stressful life events during a time interval (e.g., the period between Wave 1 and Wave 2) on the level of a personality construct at a later point in time (e.g., self-esteem or narcissism at Wave 2) controlling for the previous level of the construct (i.e., the Wave 1 levels of self-esteem and narcissism).…”
Section: The Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these differences between studies might be due to differences in sample composition, design and timing of measurement. For example, 2-wave longitudinal designs are restricted to linear change models whereas studies with multiple assessments can model nonlinear or discontinuous trajectories (Luhmann, Orth, Specht, Kandler, & Lucas, 2014). Moreover, personality changes in first-time parents might be better captured at more specific levels of personality than the broad Big Five traits, such as self-control.…”
Section: Previous Research On Parenthood and Personality Changementioning
confidence: 99%